What is a Decision? - Eilon, Samuel (Management Science, 1969)
The decision process is described as a series of steps, starting with information output and analysis and culminating in resolution, namely a selection from several available alternatives. Various aspects of rationality in decision making are reviewed and the concept of personalistic versus impersonalistic choice is discussed. It is suggested that with time management control tends to involve an increasing number of formal procedures and thereby to become more impersonalistic in character.